Review: Update of nutritional requirements of goats for growth and pregnancy in hot environments - Teixeira, I. A.M.A.; Härter, C. J.; Vargas, J. A.C.; Souza, A. P.; Fernandes, M. H.M.R. [UNESP] (Elsevier, 2024)
Goats play an important role in the agricultural business, providing valuable income sources through producing high-quality animal protein. They are widespread livestock for rural households due to their inherent resiliency, adaptability to many environments, and suitability in sustainable production systems. While goats are reared in highly diverse environments, a great portion of their population is reared in hot environments. Heat stress is known to affect goats' productive and reproductive performance negatively. However, goats can remarkably thrive in harsh conditions due to physiological, metabolic, and molecular adaptive mechanisms. In the face of it, in the last decades, the nutrition of goats, particularly their nutritional requirements, has received special attention. Research groups worldwide have dedicated their efforts to updating feeding systems for goats. Our objective was to present the recent findings on the energy and nutrient requirements of growing and pregnant goats in hot environments. Energy and protein requirements for the maintenance and growth of goats are influenced by sex and genotype only when mature weight is not considered in the models. Sex and genotype affect the efficiency of energy use for growth but do not affect the efficiency of protein use. Major mineral requirements for maintenance and growth are not affected by sex, except for magnesium. However, the phosphorus, sodium, and potassium requirements of goats raised in hot environments differ from those in the feeding systems. This difference may be related to the adaptation mechanisms goats employ to cope with the hot environmental conditions. Regarding requirements for pregnancy, there was no effect of days of pregnancy on the energy or protein requirements. The efficiency of metabolizable energy utilization for pregnancy increased with the progress of pregnancy. Mineral accretion for pregnancy differs between single and twin pregnancies and, irrespective of pregnancy type, the mineral requirements increase as pregnancy progresses. The differences between the estimated dietary requirements of goats raised in hot environments and the most widely adopted feeding systems suggest that these goats may be using energy and nutrients to cope with heat stress and other stressors associated with hot environments. The recent findings on energy, protein, and mineral requirements of growing and pregnant goats can be an important resource of information for enhancing feeding systems worldwide.
Keywords: Efficiency of utilization; Hot climate; Metabolizable energy; Metabolizable protein; Small ruminants